First record of a trophonema in black corals (Cnidaria: Antipatharia) - Lauretta, Daniel Marcelo (2018)
The gametes of many groups of anthozoans contain a funnel-shaped cluster of specialized cells that facilitate the transport of nutritive substances, known as the trophonema. This structure has been found within all orders of anthozoans, with the exception of pennatulaceans, scleractinians, and antipatharians, the latter of which are commonly known as black corals. Based on the histological study of eight specimens of the black coral Dendrobathypathes grandis Opresko (Zool Med Leiden 76(22):411–442, 2002) from the southwestern Atlantic, we report for the first time the presence of a trophonema within the order Antipatharia. A trophonema was found only in oocytes from one of the seven female specimens studied. Since D. grandis contains the largest oocytes among antipatharians that have been studied to date, it remains unknown whether the presence of a trophonema is an exceptional case, or whether these structures have simply been overlooked in other black corals.